THE ROLE OF DIGITAL TRANSFORMATION, INNOVATION MANAGEMENT, AND CHANGE READINESS IN ORGANIZATIONAL SUSTAINABILITY (Indo-Fintech Intellectuals: Journal of Economics and Business, 2025)
. In the era of rapid technological advancements and dynamic business environments, organizations must embrace digital transformation, effective innovation management, and change readiness to achieve long-term sustainability. This study examines the interplay between these factors and their collective impact on organizational sustainability. Using a quantitative research approach, data was collected from organizations undergoing digital transformation initiatives. The findings reveal that digital transformation significantly enhances sustainability by optimizing resource utilization and operational efficiency. Innovation management further contributes by fostering eco-friendly business practices and sustainable competitive advantages. Additionally, change readiness plays a crucial role in facilitating the successful implementation of digital and innovation-driven strategies. The study highlights the mediating role of innovation management and the moderating influence of change readiness in the relationship between digital transformation and sustainability. Theoretical and practical implications suggest that organizations should strategically integrate technology, innovation, and change management to achieve sustainable business outcomes. The research provides valuable insights for corporate leaders, policymakers, and academics aiming to align digital strategies with sustainability objectives.